3 - The Global Economic Crisis and the Africa Rising Narrative - Pillay, Devan (Africa Development, 2021)
As seductive as the Africa rising narrative is, this article argues that it is misleading. It draws the people of Africa into a false sense of promise – of ‘development’ and ‘decent’ jobs for all – that can never be delivered by the current economic growth paradigm. A radical rethink is needed to break out of the cycle of deepening inequality, dispossession and ecological devastation. The ‘modernisation’ paradigm based on incessant production and consumption can only meet the needs of an enclave within a sea of poverty, pollution and plunder. Africa is regarded by transnational corporations and their governments as the last piece of virgin territory left to exploit for maximum returns. This search for new avenues of accumulation must be understood in the context of the intertwined global socio-economic as well as ecological crisis, where capital acts as a spreading virus. It develops but also destroys; if left to its own devices, its destructive power is incalculable.This article situates the Africa rising narrative, and the challenges of growth and development, within the context of the global poly-crisis. It examines the economic and ecological dimensions of this continuing crisis, and asks whether Africa’s future prospects lie with mimicking the industrial development paths of Europe and North America, which leads to enclave development, or in forging a new holistic developmental path that avoids the pitfalls of dispossession, environmental injustice and rising social inequality.